PARTISIPASI WARGA DALAM GOTONG ROYONG MELALUI KOMUNITAS PENGELOLA SAMPAH RUKUN SANTOSO - Apriyani, Nurma; Muchtarom, Moh; Suryono, Hassan (Educitizen, 2017)
ABSTRACTThe purpose of this study is to (1) knowhow far of society participation in cooperation activities through the waste management communityof rukun santoso. (2) know the motivation of society participation in gotongroyong activity through the  waste management communityof rukun santoso. (3) find out what constraints faced by the society in participating the gotong royong activities throughwaste management community of rukun santosoThis study usedqualitative descriptive research. Sources of data used are informants, events or activities and documents. The sampling technique is purposive sampling. Techniques of the data collection and compilation of data were done by interviews, observation and document analysis. The researcher used data triangulation and triangulation methods to obtain valid data. While the techniques of analyzing the data using interactive models are: (1) data collection (2) data reduction (3) data presentation and (4) drawing conclusions. This research procedure follows the following steps: (1) pre-field, (2) field implementation, (3) field analysis, and (4) preparation of the research report.Based on the results of the research can be concluded that: (1) society participation in gotong royong through the waste management community of rukun santoso is good enough although not all of the society participated in gotongroyongactivity. (2) society motivation in participating gotong royong through the waste management community of rukun santoso including the environmental become healthy and clean. In adition, with the society participation of gotongroyongthrough the waste management community of rukun santoso could increase togetherness and unity among the society.(3) the constraints faced by society to participate in gotong royong through the waste management community of rukun santoso is due to the characteristic of the garbage which such a disgusting thing and not all of the young society have participated in gotong royong activities.Keyword        : Society Participation, Gotong Royong, Waste Management Community Of Rukun Santoso